Risk of post-polypectomy bleeding and thromboembolic events during colonoscopy in patients on continued or interrupted antiplatelet therapy: a pooled analysis - Shen, Nan-Nan; Ma, Jun-Hong; Qian, Hua; Fu, Yong-Ping (Frontiers in Pharmacology, 2025)
BackgroundIt remains uncertain whether antiplatelet therapy is associated with an increased risk of bleeding in patients undergoing colonoscopic post-polypectomy. Our objective was to compare the incidence of post-polypectomy bleeding and thromboembolic events among patients receiving uninterrupted and interrupted antiplatelet therapy.MethodsWe conducted a comprehensive search of PubMed, MEDLINE, and Cochrane library databases up until March 2024 to identify relevant studies. The primary outcome was the incidence of bleeding events in patients undergoing colonoscopy with polypectomy while continuing or interrupting antiplatelet therapy. Additionally, we assessed the occurrence rate of thromboembolic events as a secondary outcome measure.ResultsTwenty two studies, encompassing 95,107 patients receiving antiplatelet therapy, met the inclusion criteria. Overall, the pooled incidence of colonoscopic post-polypectomy bleeding were 2.40% for patients on uninterrupted clopidogrel, and 2.20% for those on interrupted clopidogrel therapy. Subgroup analysis revealed that older patients on clopidogrel therapy had a higher risk in both uninterrupted (4.60% vs. 1.40%) and interrupted (3.00% vs. 1.50%) treatment regimens compared to younger patients. The incidence of post-procedural bleeding for continued and interrupted aspirin was 1.70% and 1.40%, respectively. Similarly, older individuals on uninterrupted aspirin therapy exhibited a higher risk of bleeding with an incidence rate of 2.50% compared to younger individuals with an incidence rate of l.00%. Among all the regions, the European population on uninterrupted aspirin therapy demonstrated the highest bleeding incidence at 7.20%. Furthermore, thromboembolic events were more prevalent in patients on interrupted clopidogrel than those did not interrupt clopidogrel therapy.ConclusionUninterrupted antiplatelet therapy in elderly patients increases the risk of post-polypectomy bleeding, while the potential elevated risk of thromboembolic events resulting from discontinuation should not be ignored. Especially for high-risk patients, endoscopists must carefully weigh the risk of bleeding and adverse cardiovascular events when deciding whether to interrupt or continue antiplatelet therapy.